Anxiety in Arabic speaking skill among lower secondary students - Mohamed Mokhtar, Mohd Ieruwan; Che Haron, Sueraya (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh, 2019)
Students’ academic performance in speaking fluently in a foreign language classroom depends on their confidence or anxiety levels. The study aims to investigate four (4) factors for anxiety, which cause speaking anxiety among students in an Arabic Language classroom at secondary schools. As a preliminary study, total numbers of forty (40) students at the Federal Territory of Kuala Lumpur were selected based on random stratified sampling, to analyse their anxiety in Arabic as their foreign language. The four (4) issues that commonly influence students’ achievement are test anxiety, communication apprehension, anxiety in classroom and fear of negative evaluation anxiety. Hence, the researcher investigates this area of anxiety using the established questionnaire of (FLCAS) developed by Horwitz (1986). This study uses SPSS version 22.0 software application to process and interprete the data for the descriptive statistics. The descriptive statistics are the means, standard deviation and percentage, which show the significance of this study. The study will have significant contributions and suggestions for the process of learning of the Arabic language as a foreign language in daily secondary schools. The findings can help the teachers to understand students’ anxiety in the process of studying the Arabic Language, especially in Arabic speaking skill at the daily secondary schools and another secondary school in general.